2012
DOI: 10.1089/ten.tea.2011.0357
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells Combined with a Demineralized Cancellous Bone Substrate for Bone Regeneration

Abstract: Mesenchymal stem cells (MSCs) isolated from cadaveric adipose tissue can be obtained in large quantities, and have been reported in the literature to be capable of inducing bone formation in vivo and ex vivo.( 1-6 ) The hypothesis tested whether a demineralized cancellous bone matrix (DCBM) can provide an effective substrate for selection and retention of stem cells derived from the stromal vascular fraction (SVF) of adipose. Human cadaveric adipose tissue was recovered from a donor and digested. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 60 publications
5
32
0
1
Order By: Relevance
“…The two grafting materials seemed to perform in a similar way concerning their contribution to bone formation which is consistent whit other studies 1,2,4,5,20 . They appeared to be osteoconductive, leading to a mineralized bone matrix with osteoblasts and chronic inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 89%
“…The two grafting materials seemed to perform in a similar way concerning their contribution to bone formation which is consistent whit other studies 1,2,4,5,20 . They appeared to be osteoconductive, leading to a mineralized bone matrix with osteoblasts and chronic inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 89%
“…ASC-derived osteogenic precursors from both murine and rat adipose tissues, together with other animals such as rabbits, dogs, horses, rhesus monkey, and even brown bear, have also been described [63][64][65][66][67][68]. Most recently, the isolation of ASCs from human cadaveric adipose tissue and their adherence and survival on demineralized bone allografts has been reported [69], suggesting that viable ASCs for osteogenic differentiation may also be obtained from cadavers within 24 hours of their death. Using in vitro culture systems, the expression patterns of key osteogenic genes have been assessed using livecell, temporal gene expression analysis of ASC osteogenesis under dexamethasone/VD3 induction [70], and numerous studies characterize the role of key signaling pathways in this lineage [71][72][73][74][75][76][77][78].…”
Section: The Mesodermal Potential Of Ascsmentioning
confidence: 99%
“…Different sizes of mineralised bone cube required different times of demineralisation, in this report 24 h was found to demineralise all 3.4 cm 3 sponges and 48 h was found to demineralise all 8.0 cm 3 sponges. Most studies on demineralised bone have reported on ground cortical bone as the starting material and several reports have suggested that cancellous bone contains low levels of BMPs and as such are mostly osteoconductive (Mauney et al 2005), although a Cell Tissue Bank recent study indicated that cancellous bone contains similar levels of BMP2, BMP4 and BMP7 to those found in cortical bone (Shi et al 2012). In addition, the nature of the porous bony trabeculae could provide a suitable microenvironment for osteoblastic cell attachment and differentiation, again previously reported (Shi et al 2012;Smith et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on demineralised bone have reported on ground cortical bone as the starting material and several reports have suggested that cancellous bone contains low levels of BMPs and as such are mostly osteoconductive (Mauney et al 2005), although a Cell Tissue Bank recent study indicated that cancellous bone contains similar levels of BMP2, BMP4 and BMP7 to those found in cortical bone (Shi et al 2012). In addition, the nature of the porous bony trabeculae could provide a suitable microenvironment for osteoblastic cell attachment and differentiation, again previously reported (Shi et al 2012;Smith et al 2014). We have not investigated the osteoinductive potential of these larger DBM sponges, however, we have previously demonstrated that 1.0 cm 3 cancellous DBM sponges, produced using similar methodology as described here, are osteoinductive when implanted into a rodent model .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation